1998
DOI: 10.1200/jco.1998.16.3.1197
|View full text |Cite
|
Sign up to set email alerts
|

Role of the p16 tumor suppressor gene in cancer.

Abstract: Since its discovery as a CDKI (cyclin-dependent kinase inhibitor) in 1993, the tumor suppressor p16 (INK4A/MTS-1/CDKN2A) has gained widespread importance in cancer. The frequent mutations and deletions of p16 in human cancer cell lines first suggested an important role for p16 in carcinogenesis. This genetic evidence for a causal role was significantly strengthened by the observation that p16 was frequently inactivated in familial melanoma kindreds. Since then, a high frequency of p16 gene alterations were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
410
0
15

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 637 publications
(453 citation statements)
references
References 16 publications
11
410
0
15
Order By: Relevance
“…p16 INK4a acts as a retinoblastoma protein (pRB) agonist by inhibiting the phosphorylation of pRB by activated cyclin-dependent kinases 4 and 6 (2). The principal methods of p16 INK4a inactivation are homozygous deletion of the gene, promoter methylation of exon 1␣, and intragenic mutation (3). The frequency of p16 INK4a inactivation in human neoplasia rivals that of p53.…”
mentioning
confidence: 99%
“…p16 INK4a acts as a retinoblastoma protein (pRB) agonist by inhibiting the phosphorylation of pRB by activated cyclin-dependent kinases 4 and 6 (2). The principal methods of p16 INK4a inactivation are homozygous deletion of the gene, promoter methylation of exon 1␣, and intragenic mutation (3). The frequency of p16 INK4a inactivation in human neoplasia rivals that of p53.…”
mentioning
confidence: 99%
“…41 Thus, p16 inactivation by genetic mutations, allelic loss, or hypermethylation of the promoter is a common event not only in prostate cancer but also in other cancers. [22][23][24][25]42 In this study, we found that human prostate cancer was suppressed markedly with a replication-defective, recombinant, E1/E3-deleted adenovirus containing a truncated Rous sarcoma virus (RSV) promoter and the wild-type (wt) p16 tumor-suppressor gene. Animals bearing human prostate cancer xenografts treated with AdRSVp16 also had longer survival.…”
mentioning
confidence: 99%
“…12,15 The p16 protein, encoded by the gene CDKN2A on chromosome 9p, is critical to tumor suppression and has an important role in melanomas. 16,17 p16 Ink4a is a cyclin-dependent kinase inhibitor that blocks formation of the catalytically active CDK4/6-cyclin D complex, thereby preventing the phosphorylation of the retinoblastoma (Rb) gene and passage through the cell cycle's G1/S checkpoint (Figure 2a). [17][18][19][20] As a tumor suppressor, p16 is found in low levels in normal proliferating cells but events such as DNA damage, oncogenic stress, and aging trigger its Figure 1 Four scenarios from the proposed diagnostic algorithm for the assessment of the malignant potential of atypical spitzoid tumors.…”
Section: Immunohistochemical Testsmentioning
confidence: 99%